Evaluation of the mechanical properties of chemically modified chicken feather fibres reinforced high density polyethylene composites. Issue 1 (2nd January 2018) - Oladele, Isiaka Oluwole; Okoro, Avwerosuoghene Moses; Omotoyinbo, Joseph Ajibade; Khoathane, Moshibudi Caroline
ABSTRACT: Despite the effectiveness and advantages of natural fibres from plants as reinforcement in the production of composite materials, it has been observed that such fibres have limitation of a high rate of absorption of moisture. In most cases, this weakens the properties of the composites. So, there is need to divert attention into the use of other source of natural fibres such as avian fibres. In this research, brown avian fibres from chicken feathers were utilized to reinforce high density polyethylene (HDPE) for structural applications. The brown avian fibres were extracted from chicken feathers by trimming after which they were treated with 0.1 M NaOH solution. The treated and untreated fibres were analysed to ascertain their elements, crystallinity index and morphology by using Atomic Absorption Spectrophotometer, X-Rays diffraction (XRD) and scanning electron microscopy (SEM), respectively. The composites were produced by varying fibre ratio as; 2, 4, 6, 8 and 10 wt% with HDPE matrix. The composite samples were characterized to ascertain their tensile and flexural properties in accordance with ASTM D3038M-08 and ASTM D7264M-07 standards, respectively. Morphology of the composites was analysed and it revealed that chemical treatment of the avian fibres is potential by means of enhancing the properties of their corresponding composites. Composite samples reinforced with modified avian fibres displayed the best mechanical properties in terms of tensile properties and flexural modulus.